Dynamic mapping at the laminar level of odor-elicited responses in rat olfactory bulb by functional MRI - Yang, Xiaojin (The National Academy of Sciences, 1998)
We have applied functional MRI (fMRI) based on blood oxygenation level-dependent (BOLD) image-contrast to map odor-elicited olfactory responses at the laminar level in the rat olfactory bulb (OB) elicited by iso-amyl acetate (10(−2) dilution of saturated vapor) with spatial and temporal resolutions of 220×220×1,000 μm and 36 s. The laminar structure of the OB was clearly depicted by high-resolution in vivo anatomical MRI with spatial resolution of 110×110×1,000 μm. In repeated BOLD fMRI measurements, highly significant (P < 0.001) foci were located in the outer layers of both OBs. The occurrence of focal OB activity within a domain at the level of individual glomeruli or groups of glomeruli was corroborated on an intra- and inter-animal basis under anesthetized conditions with this noninvasive method. The dynamic studies demonstrated that the odor-elicited BOLD activations were highly reproducible on a time scale of minutes, whereas over tens of minutes the activations sometimes varied slowly. We found large BOLD signal (ΔS/S = 10–30%) arising from the olfactory nerve layer, which is devoid of synapses and composed of unmyelinated fibers and glial cells. Our results support previous studies with other methods showing that odors elicit activity within glomerular layer domains in the mammalian OB, and extend the analysis to shorter time periods at the level of individual glomeruli or groups of glomeruli. With further improvement, BOLD fMRI should be ideal for systematic analysis of the functional significance of individual glomeruli in olfactory information encoding and of spatiotemporal processing within the olfactory system.